Sistema multiagente para recomposição automática de subestação e redes de distribuição de energia elétrica - Barros, João Victor Cavalcante (2013)
This work presents a multi-agent system for automatic restoration of power distribution networks. The proposed system consists of three types of agents: device agent, feeder agent and substation agent. Device agents are associated with system equipment and are responsible for information acquisition of the network; the feeder agents are responsible to manage the feeders; and the substations agents are accountable of manage the network supply capability. The behaviors and interactions of the system agents during the restoration process, aiming to restore the feeder sectors affected by but not in fault, are presented. Eight case studies are presented, which test different possible situations likely to be found in the distribution systems, such as restoration by uncoordinated protection, partial recovery of the system because of operating system restrictions and recomposition for faults in the transformer substation. To validate the test cases a simulator was developed, which allows the simulation of faults in different locations of the power system under study. Through the simulator, where there are the single line diagram of the system with the state of the equipment and the tool to capture message in JADE, is possible to simulate different scenarios and observe the interaction of agents in search of system restoration. The proposed system is able to locate and isolate the fault, and restore suitably the system, considering operating limits and uncoordinated system protection.